Menelusuri Nilai-nilai Pendidikan Karakter dalam sebuah Buku Teks Bahasa Inggris Experiencing English untuk Kelas Delapan SMP - Septianingsih, Anis; Rahmawati, Maya; Saefullah, Hilmansyah (Peneliti.net, 2024)
Character education is crucial in shaping a society with decent morals and positive behavior. Developing character education can be accomplished through educational institutions such as schools which play a significant role in students’ character development. As one of the main learning resources in schools, textbooks can help facilitate the development of character education. This study aims to explore the character education values embedded in an English textbook Experiencing English for eighth grade Junior High School, and to find out how the character education values are represented in the textbook. This is a content analysis research study analyzing the data in the forms of reading texts, conversational texts, and pictures from the textbook. The results of the study show that there are a total of 18 character education values, as issued by the Ministry of National Education based on the Curriculum 2013, embedded in 49 reading texts, 17 conversational texts, and 17 pictures. Fond of reading became the most frequent character value found in the textbook with a percentage of 15.7%, while democracy with a percentage of 1.2% became the least frequent character value found. The character values embedded in the textbook are essential in shaping students to have excellent characters.